Process innovation in tourism management: A review of the literature - Damian, Irma Elia; Suárez–Barraza, Manuel Francisco (Intangible capital, 2015)
Purpose: Identifying gaps in the academic literature regarding three great management topics: Process Innovation, Tourism Management and Process Innovation in Tourism Management in order to establish the conceptual framework and identify future lines of research. Design/methodology: For this research, a systematic review was conducted on items obtained from accredited databases recognized as EBSCO, OECD, among others, the literature on Process Innovation, Tourism Management and Process Innovation in Tourism Management. Findings: As a result of this review the opportunity for academic research was identified, this due to a theoretical gap which exists on the subject of Process Innovation in Tourism Management. Research limitations/implications: For the realization of this research the databases used were: EBSCO, Emerald, OECD, ProQuest and Scientific Research. The authors are aware that there may be other papers of the subject that were not considered in this article. Practical implications: Following this research the road to research other issues is opened, such as: what impact does it have and how do Process Innovations in Tourism Management are carried along in organizations belonging to Sector Originality/value: The knowledge of how process innovation in tourism management occurs in hospitality organizations gives a better understanding and comprehension of this subjects opening the possibility, for other organizations, of adopting and adapting them in areas related to customer satisfaction, improvement of the image of the organization and quality of the service offered.